2000
DOI: 10.1007/s002040050009
|View full text |Cite
|
Sign up to set email alerts
|

Chondrotoxicity of ciprofloxacin in immature Beagle dogs: immunohistochemistry, electron microscopy and drug plasma concentrations

Abstract: The systemic effects of ciprofloxacin in immature Beagles were studied. Dogs of 10-11 weeks were dosed orally for 5 days with 0 (n=3), 30 (n=5) and 200 (n=5) mg ciprofloxacin/kg body wt. Plasma concentrations were measured by high-performance liquid chromatography (HPLC) 1 h after dosing (assuming to be peak concentrations). In view of the high doses used, the plasma concentrations were rather low and declined during the study period. For example, plasma concentrations in the high dose group were 6.6 +/- 0.9 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…Ciprofloxacin also affected the mean length of humora and femora leading to reduction in Limb length of rat pulps (Channa et al, 2008). The above reports could be consistent with the study of Stahlmann et al (2000) who reported that 200 mg kg −1 of Ciprofloxacin administered to immature Beagles induced cleft formation and erosion of joint cartilage. Male wistar rats exposed to 50mg kg −1 of Ciprofloxacin for 21 days inhibit fracture healing with decreased cartilage cellullarity and fibrous proliferation and matrix degeneration (Huddleston et al, 2000).…”
Section: Animal Studiessupporting
confidence: 92%
“…Ciprofloxacin also affected the mean length of humora and femora leading to reduction in Limb length of rat pulps (Channa et al, 2008). The above reports could be consistent with the study of Stahlmann et al (2000) who reported that 200 mg kg −1 of Ciprofloxacin administered to immature Beagles induced cleft formation and erosion of joint cartilage. Male wistar rats exposed to 50mg kg −1 of Ciprofloxacin for 21 days inhibit fracture healing with decreased cartilage cellullarity and fibrous proliferation and matrix degeneration (Huddleston et al, 2000).…”
Section: Animal Studiessupporting
confidence: 92%
“…Biochemical alterations were observed at both dose levels studied, but the low dose treatment (30 mg/kg) was not associated with clinical symptoms in four of five dogs; only at the higher dose were alterations in gait noticed in all treated dogs. Clear cut lesions in joint cartilage were detected in samples from only two of five dogs in the highdose ciprofloxacin group (200 mg/kg), as described elsewhere (Stahlmann et al 2000). In considering drug safety, it is a major concern that alterations to the pericellular matrix in tendons might be present without recognizable clinical effects until a major part of the matrix the organized collagens fibers is affected.…”
Section: Discussionmentioning
confidence: 72%
“…At the end of this treatment-free period and after the dogs had developed from juvenile to adult animals, a necropsy and histopathology investigation of weight-bearing joints was performed. This included the use of stains to investigate specifically the cartilage matrix, immunohistochemical demonstration of a 5 b 1 integrin and electron microscopy, which have been described as sensitive methods for the detection of quinolone-induced changes (Shakibaei et al 1995;Kuehner 2000;Stahlmann et al 2000). None of these animals showed any quinoloneinduced joint lesion.…”
Section: Discussionmentioning
confidence: 99%